CLONING AND CHARACTERIZATION OF HIGH RISK HUMAN PAPILLOMA VIRUS (HPV) ONCOGENE E6. - Jumaah, Karrar Abdulameer; Malla, Sudhakar; Senthil Kumar, R. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Cervical cancer has always been a burden for developing countries which suffer with considerable barriers to set up cytology-based screening programs. HPVs, also called human papilloma viruses, are a group of more than 150 related viruses. More than 40 of these viruses can be easily spread through direct skin-to-skin contact during vaginal, anal, and oral sex. HPV had been proved to play a crucial role in the development of cervical cancer. HPV mainly targets the tumor suppressor proteins via the oncogenes E6 and E7. These alter the host cell metabolism and prevents the cell from apoptosis. Viral based vaccines are very few for the HPV diagnosis. Novel methods are being developed for the production of antibodies to specific antigens and thus helping in the process of development of protein based vaccines. E6 gene was isolated and ligated into pTZ57R/T cloning vector. The ligated product was then cloned into DH5α strain and allowed to propagate. The plasmids thus cloned were purified and later expressed for the gene of interest in an expression vector. The proteins specific to the gene of interest was then isolated and purified. This proteins purified can in turn be used for protein based vaccines. Key words: HPV, E6 gene, p53, oncogenes.